2021
DOI: 10.3390/ijms22041599
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Hypothyroidism to Cognitive Impairment and Hippocampal Synaptic Plasticity Regulation in an Animal Model of Depression

Abstract: The role that thyroid hormone deficiency plays in depression and synaptic plasticity in adults has only begun to be elucidated. This paper analyzes the possible link between depression and hypothyroidism in cognitive function alterations, using Wistar–Kyoto (WKY—an animal model of depression) rats and control Wistar rats under standard and thyroid hormone deficiency conditions (propylthiouracil administration—PTU). A weakening of memory processes in the WKY rats is shown behaviorally, and in the reduction of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
4
9
0
1
Order By: Relevance
“…The models of depression and hypothyroidism used in this study were verified in our previous studies. In addition to the fact that the WKY rats are a well-described model of depression [22], in our research, conducted at the same time as the current study, we also confirmed the presence of pro-depressive behavior in the forced swim test, pro-anxiety behavior in the elevated plus-maze test and memory disturbances in the novel object recognition and novel object location test [14,31]. Moreover, in WKY rats, we also observed a reduction in long-term potentiation in the dentate gyrus and CA1 region of the hippocampus and in short-term synaptic plasticity in the CA1 region of the hippocampus in electrophysiological studies, which also indicates the presence of memory disturbances in WKY rats [14].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The models of depression and hypothyroidism used in this study were verified in our previous studies. In addition to the fact that the WKY rats are a well-described model of depression [22], in our research, conducted at the same time as the current study, we also confirmed the presence of pro-depressive behavior in the forced swim test, pro-anxiety behavior in the elevated plus-maze test and memory disturbances in the novel object recognition and novel object location test [14,31]. Moreover, in WKY rats, we also observed a reduction in long-term potentiation in the dentate gyrus and CA1 region of the hippocampus and in short-term synaptic plasticity in the CA1 region of the hippocampus in electrophysiological studies, which also indicates the presence of memory disturbances in WKY rats [14].…”
Section: Discussionsupporting
confidence: 84%
“…Samples were isolated and processed according to a protocol described previously [14]. In brief, brain structures such as the frontal cortex and hippocampus were homogenized in 2% SDS (BioShop, Burlington, ON, Canada) and prepared for the following analysis by mixing equal amounts of protein with loading buffer (Bio-Rad, CA, Hercules, CA, USA) before being boiled (5 min, 95 °C).…”
Section: Western Blot Analysis Of Tissue Homogenatesmentioning
confidence: 99%
See 1 more Smart Citation
“…UFSM, Santa Maria, v11, e53: p. 1-21, 2021 consumo de álcool, exacerbando estados negativos, principalmente na ressaca, 27 em problemas de saúde como no hipotireoidismo e na depressão. 28 No entanto, tais variáveis não comprometeram o desfecho obtido neste estudo.…”
Section: Discussão Discussão Discussão Discussãounclassified
“…On the one hand, it is recognized that disturbance in thyroid homeostasis may manifest various psychiatric symptoms, including depression, anxiety, mood swings, and psychosis, probably due to thyroid hormone-mediated interference in metabolic processes and intracellular signaling pathways ( 11 ). For example, decreased T4 levels have been linked to reduced neuronal actin polymerization in cultured astrocytes.…”
Section: Introductionmentioning
confidence: 99%